Sagot :
Answer:
-6
Step-by-step explanation:
1. Substitute the equation 3(2x + z) using the given values
2. Since x = -2, substitute the x in the equation with the value -2
Like this ------> 3[2(-2) + z)]
3. Next would be z = 2... substitute the z in the equation with the value 2
Like this ------> 3[2(-2) + 2]
4. Start solving the equation using the PEMDAS rule:
= 3[(-4) + 2]
= 3(-2)
= -6
Your final answer should be -6
[tex] \huge{ \green{ \tt{Answer:}}}[/tex]
------------------------------------------------------------------
The answer is -6.
------------------------------------------------------------------
Given:
[tex] \tt \large \: x = -2[/tex]
[tex] \tt \large \: z = 2[/tex]
Step-by-step Explanation:
[tex] \tt \large3(2x + z)[/tex]
[tex] \tt \large3(2( - 2) + 2)[/tex]
[tex] \tt \large3(( - 4 )+ 2)[/tex]
[tex] \tt \large3( - 2)[/tex]
[tex] \large\red{ \boxed{ \boxed{ \boxed{ \boxed{ \tt{ = - 6}}}}}}[/tex]
------------------------------------------------------------------